2023
DOI: 10.3390/pathogens12020258
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Anticoccidial Activity of Some Herbal Extracts against Eimeria spp. Oocysts Isolated from Piglets

Abstract: Coccidiosis in pigs seldom results in important economic losses. However, it can influence growth rates in weaners and it is an important hygiene indicator in swine farms. Certain herbs, along with their extracts, have been used over the course of history in traditional medicine. The aim of this study was to evaluate the in vitro anticoccidial effects of Allium sativum L. (garlic), Artemisia absinthium L. (wormwood), Coriandrum sativum L. (coriander), Cucurbita pepo L. (pumpkin), Satureja hortensis L. (summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The results of this study showed a correlation between diclazuril (R 2 = 0.82) and OFI flower extract (R 2 = 0.91) concentrations in reducing the oocyst numbers ( Figure 3 ). Biological compounds, such as polyphenols, tocopherols, and flavonoids, have demonstrated strong in vitro and in vivo anticoccidial properties [ 52 , 55 , 56 ]. Furthermore, Debbou-Iouknane et al [ 22 , 23 ] showed that leaf olive extracts rich in natural polyphenolic components, such as quercetin and oleuropein, possess the ability to destroy Eimeria spp.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed a correlation between diclazuril (R 2 = 0.82) and OFI flower extract (R 2 = 0.91) concentrations in reducing the oocyst numbers ( Figure 3 ). Biological compounds, such as polyphenols, tocopherols, and flavonoids, have demonstrated strong in vitro and in vivo anticoccidial properties [ 52 , 55 , 56 ]. Furthermore, Debbou-Iouknane et al [ 22 , 23 ] showed that leaf olive extracts rich in natural polyphenolic components, such as quercetin and oleuropein, possess the ability to destroy Eimeria spp.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro study, C. pepo and C. sativum alcoholic extracts demonstrated strong anticoccidial effects against Eimeria spp. oocysts isolated from swine [ 57 ]. Several studies have shown that coriander seed supplements used in poultry feed acted as an alternative to antibiotics and antiparasitics, reducing cholesterol levels and improving both blood parameters and growth performance [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%